IMPROVING FINANCIAL LITERACY AND PERCEPTION TO INCREASE PUBLIC INVOLVEMENT IN CAPITAL MARKETS: EVIDENCE IN INDONESIA - Dito Rinaldo; Vina Anggilia Puspita; Nico Irawan (Faculty of Economics and Business Udayana University, 2025)
The insufficient financial literacy of the Indonesian people causes low public involvement in the capital market; thus, this study seeks to build a capital market education model that can be a solution to this problem. The SEM-PLS technique was used to test hypotheses on 155 people from West Java. The findings of this study show that the financial literacy level of the Indonesian people is still very poor, their knowledge of investment and managing emergency funds is very restricted, and their lifestyle tends to be consumptive. Also, there is still a negative view of capital market perception, which makes people hesitant to join the market. In contrast to earlier research, this study proposes a novel capital market education model based on the findings of variable tests and indicators, with the expectation that it would be used to increase literacy and improve public perceptions of the capital market.